2014
DOI: 10.5194/acp-14-6395-2014
|View full text |Cite
|
Sign up to set email alerts
|

Extensive spatiotemporal analyses of surface ozone and related meteorological variables in South Korea for the period 1999–2010

Abstract: Abstract. Spatiotemporal characteristics of surface ozone (O 3 ) variations over South Korea are investigated with consideration of meteorological factors and timescales based on the Kolmogorov-Zurbenko filter (KZ filter), using measurement data at 124 air quality monitoring sites and 72 weather stations for the 12 yr period of 1999-2010. In general, O 3 levels at coastal cities are high due to dynamic effects of the sea breeze while those at the inland and Seoul Metropolitan Area (SMA) cities are low due to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 62 publications
2
61
0
Order By: Relevance
“…Higher concentrations of the CNSP pollutants appeared in large cities (e.g., the SMA) more often than in suburban/rural areas. However, the O 3 values were lower over the large cities than over either their outer or coastal regions due to its reaction with other air pollutants and meteorological conditions (Seo et al, 2014). According to their study, the O 3 values over the large cities were low because of the NO titration, even during the night without photochemical reactions by local anthropogenic precursor emissions, while they were high in the coastal areas because of the sea breeze effect.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Higher concentrations of the CNSP pollutants appeared in large cities (e.g., the SMA) more often than in suburban/rural areas. However, the O 3 values were lower over the large cities than over either their outer or coastal regions due to its reaction with other air pollutants and meteorological conditions (Seo et al, 2014). According to their study, the O 3 values over the large cities were low because of the NO titration, even during the night without photochemical reactions by local anthropogenic precursor emissions, while they were high in the coastal areas because of the sea breeze effect.…”
Section: Methodsmentioning
confidence: 99%
“…Seo et al (2014) revealed that the longterm trends of the local precursor emissions in O 3 in South Korea could affect the O 3 trends locally, and in the country, significant enhancement of the background O 3 negatively affected the air quality. In order to understand the negative relationship in trend between O 3 and CNSP pollutants, particularly NO 2 , we have investigated the relationship (i.e., correlation and weekly cycle) among O 3 , NO 2 and VOCs with the land-use types further in Sects.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations